Valuation In The Constitutional Era - Elmien du Plessis (Potchefstroom Electronic Law Journal, 2015)
The Constitution brought about a new compensation regime for expropriations. Compensation for expropriation must now be "just and equitable". Whereas before the Constitution came into force market value played a central role in compensation for expropriation, market value is now only one factor or aspect of compensation that the court needs to take into account. Yet we find that courts tend to focus on market value and to still employ the valuation methods used to calculate market value. This article argues that the methods used to calculate the market value, once thought to be objective, are not as objective as was believed. While it is impossible to give judges specific tools for the assessment of market value, this article provides guidelines on how the calculation of compensation should be approached.